Implementation of Islamic Spiritual Guidance in Reducing the Anxiety Level of CVA (Cerebro Vascular Accident) Patients at Muhammadiyah General Hospital in Bandung Tulungagung - Agustin Widyowati; Yudit Violitha; Anik Nurhidayah (Journal Of Nursing Practice, 2022)
Background: The incidence of stroke is still high and contributes to high mortality and disability rates. Stroke attacks cause malfunctions such as paralysis and difficulty communicating so that patients will experience anxiety, fear, sadness and even despair in the face of the disease they are suffering from. Purpose: The purpose of this study was to analyze the effect of providing Islamic spiritual guidance on the anxiety level of CVA (Cerebro Vascular Accident) patients. Methods: This research was conducted in the Inpatient Room at RSU Muhammadiyah Bandung Tulungagung using a quasi experimental design with a one group pre post test design approach, 122 respondents were taken using purposive sampling technique. The independent variable is the provision of Islamic spiritual guidance and the dependent variable is the level of anxiety using a questionnaire and Wilcoxon test analysis. Results: The results of the Wilcoxon test analysis value negative ranks N: 91, Mean: 49.23, Sum of ranks: 4480.00, so it can be concluded that there is a decrease in the value of the anxiety level before to after Islamic spiritual guidance. Based on statistical tests obtained p value: 0.001 <0.05, meaning that there is effectiveness after Islamic spiritual guidance in reducing the anxiety level of stroke patients. Islamic spiritual guidance is effective in reducing anxiety in stroke patients, so hospitals need to make a formulation to form a spiritual guidance team that can provide spiritual services to all patients in the hospital. Conclusion: Islamic spiritual guidance can reduce anxiety in stroke patients so hospitals need to make formulations to create teams or increase the ability of health workers about spiritual guidance given to all patients in the hospital.